The critical analysis of scenario construction in the Polish foresight initiatives - Nazarko, Joanicjusz; Kononiuk, Anna (Technological and Economic Development of Economy, 2013)
The aim of the article is to present the diagnosis of scenario method application in the Polish foresight initiatives. The concept of scenario method, its evolution, the state of the art of the Polish foresight studies and the critical analysis of the application of this method have been presented. From the questionnaire results the authors have identified (i) the approach used in scenario construction, (ii) the most important phases of scenario construction, (iii) the interconnection of scenario method with other methods of scenario construction, (iv) the profile of experts involved in foresight projects, (v) the profile of experts involved in scenario construction, (vi) the application of the triangulation principle in scenario construction, (vii) the application of wild cards in scenario construction and techniques to identify them, (viii) the average time of scenario construction process, (ix) the linkage of scenarios to other documents, (x) the number of scenarios elaborated upon, and (xi) the main difficulties in the process of scenario construction. To achieve article aims there have been used the following research methods: a literature review, the method of critical analysis and logical construction, survey research, the status of Polish foresight projects, interim and final report analysis. The research has been funded by the National Science Centre in Poland within a research project entitled Scenarios in future shaping and anticipation for foresight studies, project number: 4194/B/H03/2011/40.